Combined sterilizing effects of nano-ZnO and ultraviolet on convenient vegetable dishes. Issue 2 (May 2015) - Yu, Ning; Zhang, Min; Islam, Md Nahidul; Lu, Liqun; Liu, Qian; Cheng, Xinfeng
Abstract To develop a new microbial control method for ready-to-eat convenient dishes, a combined treatment of nano-ZnO and UV treatment was tested. Here, the bacteriostasis of nano-ZnO treatment was studied and compared with potassium sorbate and sodium benzoate treatments. The results showed that microbial growth rate was substantially reduced under nano-ZnO treatment for convenient dishes. Moreover, the combined effect of UV irradiation and nano-ZnO, as a non-thermal treatment, was highly researched to improve loss of texture, color and nutrition constituents of green vegetable. According to the Response Surface Methodology (RSM), nano-ZnO was applied at 0.04 g/Kg, and UV intensity and time were 196.98 V and 47.79 min respectively. The applied treatment was found successful as it showed an effective control of microorganisms along with a slight change in physical and chemical characteristics compared to traditional thermal sterilization.